Latin American Women Filmmakers : Social and Cultural Perspectives - Roberts-Camps, Traci, 1975- (Book collections on Project MUSE., 2017)
"Women are noticeably marginalized from the Latin American film industry, with lower budgets and inadequate distribution, and they often rely on their creativity to make more interesting films. This book highlights the voices and stories of some of these directors from Brazil, Chile, Argentina, and Mexico. Roberts-Camps's insightful exploration is the most broad-ranging account of its kind, making the book relevant to the study of literature as well as film."--